EFEMP1 Overexpression Contributes to Neovascularization in Age-Related Macular Degeneration - Cheng, Lu; Chen, Chong; Guo, Wenke; Liu, Kun; Zhao, Qianqian; Lu, Ping; Yu, Fudong; Xu, Xun (Frontiers in Pharmacology, 2021)
Purpose: Age-related macular degeneration (AMD) is one of the leading causes of blindness, and choroidal neovascularization (CNV) in AMD can lead to serious visual impairment. Gene expression profiling of human ocular tissues have a great potential to reveal the pathophysiology of AMD. This study aimed to identify novel molecular biomarkers and gene expression signatures of AMD. Methods: We analyzed transcriptome profiles in retinal-choroid tissues derived from donor patients with AMD in comparison with those from healthy controls using a publicly available dataset (GSE29801). We focused on the EFEMP1 gene, which was found to be differentially upregulated in AMD, especially in wet AMD eyes. Serological validation analysis was carried out to verify the expression of EFEMP1 in 39 wet AMD patients and 39 age- and gender-matched cataract controls, using an enzyme-linked immunosorbent assay (ELISA). We then investigated the role of EFEMP1 in angiogenesis through in vitro experiments involving EFEMP1 overexpression (OE) and knockdown in human umbilical vein endothelial cells (HUVECs). Results: An increase in EFEMP1 expression was observed in the retinal-choroid tissues of eyes with AMD, which was more significant in wet AMD than in dry AMD. In addition, there was a significant increase in serum fibulin-3 (EFEMP1 encoded protein) concentration in patients with wet AMD compared with that in the controls. Tube formation and proliferation of EFEMP1-OE HUVECs increased significantly, whereas those of EFEMP1 knockdown HUVECs decreased significantly compared with those of the control. Additional extracellular fibulin-3 treatments did not increase tube formation and proliferation of wildtype and EFEMP1 knockdown HUVECs, indicating that the proangiogenic properties of EFEMP1 are of cell origin. We also found that vascular endothelial growth factor expression in HUVECs was upregulated by EFEMP1 overexpression and downregulated by EFEMP1 knockdown. Conclusion: Our findings demonstrate EFEMP1 as a novel biomarker for CNV in AMD, providing a new target for the development of wet AMD-directed pharmaceuticals and diagnostics.